Answer:
Explanation:
5
+
1
=
3
+
7
5x+1=3x+7
Solve
1
Subtract
1
1
from both sides of the equation
5
+
1
=
3
+
7
5x+1=3x+7
5
+
1
−
1
=
3
+
7
−
1
5x+1{\color{#c92786}{-1}}=3x+7{\color{#c92786}{-1}}
2
Simplify
Subtract the numbers
Subtract the numbers
5
=
3
+
6
5x=3x+6
3
Subtract
3
3x
from both sides of the equation
5
=
3
+
6
5x=3x+6
5
−
3
=
3
+
6
−
3
5x{\color{#c92786}{-3x}}=3x+6{\color{#c92786}{-3x}}
4
Simplify
Combine like terms
Combine like terms
2
=
6
2x=6
5
Divide both sides of the equation by the same term
2
=
6
2x=6
2
2
=
6
2
\frac{2x}{{\color{#c92786}{2}}}=\frac{6}{{\color{#c92786}{2}}}
6
Simplify
Cancel terms that are in both the numerator and denominator
Solution
=
3